2021
DOI: 10.1136/bmjopen-2020-044221
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of patients’ experiences, needs and expectations regarding online access to their primary care record

Abstract: ObjectivesPrimary care records have traditionally served the needs and demands of clinicians rather than those of the patient. In England, general practices must promote and offer registered patients online access to their primary care record, and research has shown benefits to both patients and clinicians of doing so. Despite this, we know little about patients’ needs and expectations regarding online access to their record. This study explored what patients and carers want from online access to their electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…Our study was focused on the primary care staff perspective, but importantly, the findings support previous research from the patient perspective which emphasises the opportunities and challenges of patient access to EHRs. Studies exploring this perspective have reported similar issues; for example secure access and confidentiality, implications for health inequalities, and benefits for self-monitoring [ 34 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study was focused on the primary care staff perspective, but importantly, the findings support previous research from the patient perspective which emphasises the opportunities and challenges of patient access to EHRs. Studies exploring this perspective have reported similar issues; for example secure access and confidentiality, implications for health inequalities, and benefits for self-monitoring [ 34 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Open notes offer patients unprecedented transparency to their healthcare. Encouragingly, a growing body of research in countries where the practice is advanced demonstrates that the majority of patients who access their notes derive multiple benefits including greater understanding about their treatments, better recall about treatment plans, greater engagement in their care, and enhanced understanding about the rationale for prescribed treatments and interventions 78 79 81 87–89. However, as this paper has argued, there may also be unintended negative consequences associated with this change of practice, including the potential to increase nocebo effects 90.…”
Section: Ethical Implicationsmentioning
confidence: 90%
“…GPs have previously expressed concerns that patient access to records could increase risks of litigation and require them to change the way they write on the records so that patients can understand them 39 . Patients have expressed a need for support and training in using and understanding the online record 40 . A systematic review of patient record sharing in UK secondary care found that the approach of giving information to patients almost exclusively verbally was insufficient; and patients should have access to notes, but that simply allowing full access, without explanation or summary, is also insufficient 41 .…”
Section: Summary Report Comparison With Literaturementioning
confidence: 99%